2017
DOI: 10.1016/j.ebiom.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to Ipratropium Bromide in Male and Female Patients with Mild to Moderate Chronic Obstructive Pulmonary Disease

Abstract: IntroductionAlthough the prevalence of chronic obstructive pulmonary disease (COPD) is similar between men and women, current evidence used to support bronchodilator therapy has been generated in therapeutic trials that have predominately enrolled male patients. Here, we determined whether there is any significant sex-related differences in FEV1 responses to ipratropium bromide.MethodsData from the Lung Health Study (n = 5887; 37% females) were used to determine changes in FEV1 with ipratropium or placebo in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…In COPD patients, this effect might be localized to less affected parts. Clinical outcomes of ipratropium bromide in COPD are presented elsewhere [19]. Ipratropium bromide had little effect in newborn CF piglets indicating that initial CF disease is acting by a different mechanism than in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD patients, this effect might be localized to less affected parts. Clinical outcomes of ipratropium bromide in COPD are presented elsewhere [19]. Ipratropium bromide had little effect in newborn CF piglets indicating that initial CF disease is acting by a different mechanism than in COPD.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In addition, the human lung transcriptome has been demonstrated to have both age and gender associations, suggesting that the genes contributing to lung health and disease during adulthood will vary across the life course. 24 Gender differences in the reporting, access, or response to available treatment modalities is also a possibility, 25 , 26 although more work is needed to better understand the underlying pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior results have highlighted important sex and gender differences in men and women with COPD, the modeling of age by gender interactions across the fifth through eighth decades of life is a point of novelty and highlights the clinical imperative to more effectively and thoroughly recognize and manage respiratory symptoms in women. More research is needed to fully understand the pathogenesis of increased severity of COPD in women and to develop gender-targeted management approaches 24 , 31 to improve outcomes across the life course for both men and women with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies suggest that it is more difficult for women to quit smoking, but data from the Lung Health Study also suggest that smoking cessation results in greater lung function improvement for women (56). Additional data from the Lung Health Study also suggest greater FEV 1 response to inhaled ipratropium for women, possibly due to greater M3 relative to M2 receptor expression in women (57), and a pooled analysis of indacaterol/glycopyrronium studies reported greater quality-of-life improvements in women (58). Taken together, the compendium of evidence suggests that gender-specific approaches to COPD are imperative.…”
Section: Copdmentioning
confidence: 99%